Lipoprotein profile in girls with asymptomatic hyperuricemia - S. I. Maljavskaya; T. A. Toropygina; V. E. Tril; V. A. Ternovskaya (Российский кардиологический журнал)
To investigate the relation between uricemia and lipid profile, 539 Arkhangelsk schoolgirls aged 7-17 were examined. With upper norm limit of 0. 31 mmol/l, the prevalence of asymptomatic chronic hyperuricemia among Arkhangelsk girls was as high as 25 %. With uricemia higher than 0. 31 mmol/l, total cholesterol, triglycerides, LDL cholesterol levels were significantly elevated. Mean total cholesterol levels in such individuals were higher than WHO norms of normocholesterolemia for children and adolescents. From the other hand, among individuals with dyslipidemia, uricemia more than 0. 31 mmol/l was diagnosed significantly more frequently. All measured lipid and liporotein parameters directly correlated with uricemia level, and inversely correlated with urate excretion rate, regardless of pathogenetic hyperuricemia mechanisms. Our results point to the fact that chronic hyperuricemia is assosiated with atherogenic lipid/lipoprotein phenotype, observed as early as in childhood, and possibly acts as an indicator of atherosclerosis risk. Therefore, use of a lower norm for population screening seems rational, from position of primary and secondary prevention of atherosclerosis. Our data support detailed examination of lipid metabolism if uricemia is higher than 0. 31 mmol/l.